1999
DOI: 10.1021/js980337n
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of insulin using pH‐responsive complexation gels

Abstract: The goal of oral insulin delivery devices is to protect the sensitive drug from proteolytic degradation in the stomach and upper portion of the small intestine. In this work, we investigate the use of pH-responsive, poly(methacrylic-g-ethylene glycol) hydrogels as oral delivery vehicles for insulin. Insulin was loaded into polymeric microspheres and administered orally to healthy and diabetic Wistar rats. In the acidic environment of the stomach, the gels were unswollen due to the formation of intermolecular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
222
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(236 citation statements)
references
References 17 publications
3
222
0
4
Order By: Relevance
“…In some of the experiments, a small increase in BGL above the baseline is observed. This increase may be attributed to metabolic changes and endogenous secretion of glucagon in the diabetic rats due to stress in the animals during blood sampling (38,39). In both the p.o.…”
Section: Resultsmentioning
confidence: 99%
“…In some of the experiments, a small increase in BGL above the baseline is observed. This increase may be attributed to metabolic changes and endogenous secretion of glucagon in the diabetic rats due to stress in the animals during blood sampling (38,39). In both the p.o.…”
Section: Resultsmentioning
confidence: 99%
“…It has been stated earlier that the enteric polymers are generally used either to protect the acid-labile drugs (e.g., peptides and penicillin-G) from the harsh environment of the stomach or to avoid the contact of the gastric mucosa with the gastric-irritant drugs (e.g., ibuprofen, indomethacin), which might lead to gastric mucosa perforations. Akiyama and co-workers developed such an enteric system using poly(acrylic acid) product, which inhibited the hydrolytic activity of trypsin [53]. The oral delivery of insulin employing the use of enteric polymers is gaining importance [54].…”
Section: Matrix Systemmentioning
confidence: 99%
“…Lowman et al 5 demonstrated the potential of these environmentally sensitive complexation hydrogels to be used as a carrier for oral protein delivery, by delivering insulin to diabetic rats and lowering blood glucose levels. In addition, Madsen and Peppas 6 determined that the calcium binding properties of ionized MAA inhibit some proteolytic degradation of the released protein, therefore increasing the amount of bioactive protein transported across the epithelial layer.…”
Section: Introductionmentioning
confidence: 99%